Penerapan Konsep ‘Pemaafan Hakim’ sebagai Alternatif dalam Menurunkan Tingkat Kriminalitas di Indonesia - Hakim, Lukman (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2019)
A large number of criticisms on the effectiveness of imprisonment, which in reality cannot decrease the level of criminality in a particular country so other alternatives are required to solve this problem. Besides, this research revealed that judges in Indonesia tend to determine the imprisonment verdict on the criminal act with a criminal charge of under 5 (five) years that classified as minor criminal. The concept of Judicial Pardon along with the Purpose of Punishment will be applied in the Draft of the Criminal Code (RKUHP) has been implemented in several countries also one of the alternative penal measures to short imprisonment and judicial corrective to the legality principle, which in the end is expected the concept can decrease the level of existing criminality.